METADISCIPLINARITY OF MODERN PHILOSOPHY IN OPTICS OF PRACTICAL DIMENSIONS - Komisar, Liudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
In the introduction, the article considers issues related to the current challenges of transformation in the fields of modern humanities and philosophy in metadisciplinary dimensions. The aim of the research is to explore new optics of philosophical metadisciplinarity on the horizon of intercultural communication and educational practices in modern higher education. The problematics of the article involve the use of interdisciplinary research methods: structuralist-phenomenological, logical-analytical, ethical-axiological, cultural-philosophical, hermeneutic- ontological, and comparative. In the research results, special attention is paid to the correlation between the primary groups of concepts present in the article, such as intersubjectivity / interculturality; common world / interworld / interdisciplinarity; multidisciplinarity / metadiscursiveness. The article introduces the author’s ideas regarding the need for reactualization at the level of meta- and multidisciplinarity of modern philosophical studies in the light of practical dimensions of teaching philosophical disciplines in higher education. The substantiation of problems in the inter-/ transdisciplinary vector is exemplified in the analysis of teaching the discipline “Philosophy of science and methodology of humanitarian knowledge” for training doctors of philosophy at the Kyiv National Linguistics University. The discussion demonstrates the approbation dimensions of metadisciplinary trends in philosophy and humanities exemplified in scientific and practical conferences and educational practices in modern higher education. The conclusions demonstrate that modern multimodal combinations of specific scientific knowledge and the categorical apparatus of philosophy contribute to the emergence of innovative metadisciplinary trends, and the future of both science and philosophy is based on inter-, poly-, and meta-discursiveness.